Kemampuan Variasi Umpan Dalam Mengendalikan Vektor Tikus Di Pabrik Beras Kecamatan Tanete Rilau Kabupaten Barru - Wahyuni, Sri; Sulasmi, Sulasmi; La Taha , La Taha (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Mice are disease-carrying animals that transmit various diseases. Currently, the rat-borne disease that is a major problem in Indonesia is leptospirosis, an infectious disease caused by leptospira bacteria. This study aims to see the ability of variations of the bait used in order to control the rat population in the Rice Factory. This type of research is quasi-experimental by looking at the ability of mouse traps with bait variations in controlling rats. Data were analyzed using a one-way ANOVA statistical test using the SPSS computer program and the data that had been analyzed was then presented in tabular form. The results of this study indicated that the three types of bait used in the study were capable of being used as trapping bait and the other bait was incapable of being used as trapping bait where the total number of rats caught was 5 out of 24 traps installed. The details of the bait are as follows sweet corn bait with a presentation of 12.5% from 3 rats, purple sweet potato bait with a presentation of 4.17% from 1 rat, and cassava with a presentation of 4.17% from 1 rat. The conclusion obtained from this study is that more mice are trapped in sweet corn bait than sweet potato and cassava bait, so it is suggested to rice factory owners to keep the environment clean around the factory so that rats do not breed. Keywords: Rats, Rice Mills, and Bait Variations